Marketing Strategy through E-Commerce at UMKM Queen Burger and Snack - Tasnim Lubis; Eddy Setia; Amalia; Halimatusakdiah; Nurul Adilla Alatas Abus (Indonesian Scientific Journal, 2021)
The empowerment community program aimed to describe the use of e-commerce as a strategy to increase the marketing of UMKM Queen and Burger Snack. The condition of drastic decline experienced by business partners during the COVID-19 pandemic situation had an impact on sales and income. Unpreparedness to face the changing situation from offline to online sales is also a major problem in running a business for the owners of Queen Burger and Snack. Therefore, the team of empowerment community program (ECP) did an effort to help increase marketing through e-commerce strategies. The solution provided by the ECP team was to prepare a forum in the form of a website to convey information to readers (consumers) about the products produced by Queen Burger and Snack. Other preparations include assisting and accompanying business partners for six months to strengthen the use of e-commerce strategies in product marketing and preparation at key sales locations in production houses.